Parasites contribute to ecologically dependent postmating isolation in the adaptive radiation of three-spined stickleback. - El Nagar, Aliya; MacColl, Andrew D.C. (The Royal Society, 2016)
Spatial variation in parasitic infections is common, and has the potential to drive population divergence and reproductive isolation of hosts. However, despite support from theory and model laboratory systems, not much strong evidence has been forthcoming from the wild. Here we show that parasites are likely to cause reproductive isolation in the adaptive radiation of three-spined stickleback. Adjacent wild populations on the Scottish island of North Uist differ greatly and consistently in the occurrence of different parasites that have substantial effects on fitness. Lab-reared fish are more resistant to experimental infection by parasite species from their own population. Furthermore, hybrid backcrosses between the host populations are more resistant to the parasites from the parental population to which they are more closely related. These patterns provide strong evidence that parasites can cause ecological speciation, by contributing to selection against migrants and ecologically dependent postmating isolation.